Research on predictive control strategies for direct-drive wind turbines under power grid fault - ZHANG Yuewei; HAN Minxiao; ZHANG Mingyang (Diance yu yibiao)
The active/reactive dynamic characteristics of the wind turbine are the key factors affecting the fault ride-through characteristics and the grid-connected voltage when a fault occurs in the power grid. To solve the problems of slow tracking speed and complex control loop design of traditional proportional-integral (PI) control, a model predictive control (MPC)-based LVRT control strategy is proposed. Firstly, MPC is used instead of the current inner-loop in the control loop of the network-side converter to improve the transient characteristics during fault ride-through. Then, in the case of asymmetric voltage dips, a more concise control loop is designed by combining the latest grid entry standards to derive the command values. Finally, two sets of simulations are carried out on MATLAB/Simulink platform to verify the symmetrical and asymmetrical faults. In the case of symmetrical faults, it is verified that the proposed control strategy has better transient characteristics and can better cope with grid faults and provide reactive power support compared with the traditional control and fuzzy PI control. In the case of asymmetric faults, the proposed control strategy is verified to be effective in reducing the three-phase voltage unbalance through simulation.